Integrasi Keilmuan Berbasis Interdisipliner: Paradigma Baru Pendidikan Islam dalam Menjawab Dinamika Era Kontemporer - Siswahyuningsih, Zahrotunnisa; Adzhar, Moh. Hanif (Ngaos: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to examine the integration of science through an interdisciplinary approach as a strategy to bridge the gap between religion and science. Using a literature review method, this study begins by determining the research subject, namely the integration of science, and the research object, namely interdisciplinary studies in Islamic education. Literature collection began with the analysis of 20 valid articles from national and international journals that are indexed and accredited. The findings of this study present a unique new paradigm for Islamic education, where strengthening interdisciplinary studies through a curriculum based on current issues, developing collaborative learning methods, and integrating multidisciplinary research are feasible. In addition, improving 21st-century competencies (technological literacy, critical thinking, analytical thinking, and contextual thinking) is important in maintaining the relevance of adaptive Islamic education. The implications of this research offer a framework that can be applied as a reference for policymakers in curriculum development and for educators in designing learning. Theoretically, this research describes a more specific model of interdisciplinary integration while emphasising it as an essential new paradigm. Practically, this research contributes to strengthening the curriculum, learning methods, and the development of holistic learning competencies. However, this research has limitations as it only covers a small part of the dimensions of Islamic education, thereby opening opportunities for further research, particularly regarding learning design, media, and learning strategies through the new paradigm offered.